The Effect of â€œQuizizz Applicationâ€ on Studentsâ€™ Learning Interest and Reading Comprehension at SMAN 1 Raha - Kabil, Muhamat; Kamaluddin, Kamaluddin; Alberth, Alberth (Journal of Teaching of English, 2021)
This present study aimed to examine the effect of Quizizz application on students’ learning interest and reading comprehension at SMAN 1 Raha. This study was quantitative and the design was quasi-experimental. The technique of sampling was purposive sampling in XI MIA3 as experimental class and XI MIA4 as control class. The class of XI MIA3 consists of 30 students and XI MIA4 consists of 32 students. In collecting the data, the researcher used the questionnaire to obtain data about students’ learning interest, and the test was used to obtain the data of students’ reading comprehension. The result of the questionnaire showed that there is no positive effect of Quizizz application on students' learning interest. Based on the result analyzed of independent sample t-test. The result showed that the value of sig (2- tailed) 0.073 was higher than sig 0.05. It means the that Quizizz application does not have a positive effect on students’ learning interest. While the finding of learning outcomes showed that there was a positive effect of Quizizz application on students’ reading comprehension. It was proved by the result of the independent sample t-test analyzed on SPSS 25, the value of sig (2-tailed) 001was lower than sig 0.05. It could be concluded that the use of the Quizizz application has a positive effect on students’ reading comprehension. From those findings, it could be concluded that the use of Quizizz application on students’ learning interest did not have a positive effect while on students’ reading comprehension had a positive effect.